2024
DOI: 10.1007/s11259-024-10351-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of resistance against to flumethrin using against Varroa destructor in Türkiye

Ender Yarsan,
Fatih Yilmaz,
Sedat Sevin
et al.

Abstract: The honeybee ectoparasite Varroa destructor is a major threat to apiculture when evaluating bee diseases and pests. While attempting to control this mite, beekeepers often depend on a small selection of authorized synthetic acaricides, such as flumethrin, which is widely used in Türkiye and globally. However, resistance to flumethrin develops due to incorrect and excessive use. In this study conducted at Ordu Beekeeping Research Institute, trial group were established including an untreated control group and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Likewise, 52.8% of mites carried the homozygous G/G genotype in the group of surviving mites, compared to 71.2% among the perished mites. To determine LC 90 , the results obtained for the two additional apiaries in 2021 were compiled with the results obtained for two other apiaries sampled in 2020, resulting in an estimate of the LC 90 of 25 ppm [CI95: [21][22][23][24][25][26][27][28][29]. The coefficient of determination (R 2 ) obtained was 0.7, which indicates a good prediction of linear regression, and the correlation coefficient (r) was 0.8, indicating a high correlation strength between the variables of acaricide concentration and percentage of mortality effect.…”
Section: Genotyping Of Varroa Mites Previously Tested In the 2020 Lab...mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, 52.8% of mites carried the homozygous G/G genotype in the group of surviving mites, compared to 71.2% among the perished mites. To determine LC 90 , the results obtained for the two additional apiaries in 2021 were compiled with the results obtained for two other apiaries sampled in 2020, resulting in an estimate of the LC 90 of 25 ppm [CI95: [21][22][23][24][25][26][27][28][29]. The coefficient of determination (R 2 ) obtained was 0.7, which indicates a good prediction of linear regression, and the correlation coefficient (r) was 0.8, indicating a high correlation strength between the variables of acaricide concentration and percentage of mortality effect.…”
Section: Genotyping Of Varroa Mites Previously Tested In the 2020 Lab...mentioning
confidence: 99%
“…In several research studies, single-nucleotide polymorphisms (SNPs) were identified as the source of tau-fluvalinate and/or flumethrin resistance in Varroa mites. Although the location of SNPs in the mites’ genome varied geographically, the main target mechanism of the detected variations appeared to be the same: an alteration in the voltage-gated sodium channels, the main target site for pyrethroids [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation